Smart gardening system / Varunesh Visvalingam ... [et al.] - Visvalingam, Varunesh; Yogendran, Harrish; Visvalingam, Divyaa; Yogendran, Harchalar (Universiti Teknologi MARA, Kedah, 2019)
Smart Gardening System is a unique system. The waste from plants such as dry leaves, grass and twigs are grilled in our specially designed metal container called Smart Gardening System. It will reduce the production of smokes as heat from the sun will grill the waste slowly in the container. The magnifying glass will be powered by the solar which is placed on top of the ash funnel to produce heat thus grill the waste plantations. An iron sieve which placed in the middle between the funnel and the ash collector tank so that only tiny particles of ashes will be brushed to the ash tank. The ashes in the ash tank collector will be sprayed to the plants. The objectives are to produce natural fertilizer and pesticides. It will also produce non chemicals vegetables. The usage of waste materials will minimize environmental pollution. This project will reduce man power to run the plantations. We collect data by observation. The growth of plants recorded for 6 weeks. The observation recorded in the table and bar chart. The data shows that the plants that use chemical fertilizer produce more number of yields and the vegetables are bigger in size but it is not good for our health. Furthermore, the plants which use natural fertilizer produce healthy and greenish vegetables. Ash can be use as natural fertilizer and pesticides for vegetables and are free from harmful chemicals. It is also less prone to diseases and increases life span of human. This system is portable and friendly to ecosystem. This method ensures that the vegetables produced are from harmful chemicals. The consumers who eat these vegetables are less prone to diseases. Students can use the free time in proper way and bring awareness about natural fertilizer. It also creates awareness of agricultural market.